Optimization of concentration process on pomelo fruit juice using response surface methodology (RSM) - Keshani, Samaneh; Abdullah, Luqman Chuah; Mobarekeh, Mohsen Nourouzi; Abdul Rahman, Russly; Bakar, Jamilah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Within the globalization of the food industry, the demand for quality juice and juice type beverages has expanded. The pomelo fruit has recently gained attention because of its antioxidant capacity as studies found extracts of carotenoids, phenolics, vitamin C, lycopene, and anthocyanin. Concentration of fruit juices is important due to their low water activity, have a higher stability than single-strength juices. To reduce the storage and shipping costs, and to achieve longer storage, fruit juices are usually concentrated by multi-stage vacuum evaporation. In this work vacuum evaporation method was applied to concentrate pomelo juice. Response surface methodology (RSM) was applied to investigate the effects of the three main independent parameters; rotation, temperature and time on the pomelo juice concentration and optimizing the operating conditions of the treatment process. It is clear from the result that the concentration increased when the temperature, rotational speed and time increased. It can be inferred that any parameters, individually, had positive effect on increase of concentration. The main effects of parameters are in following order: Main effect of time> temperature> rotational speed.